Feasibility and Short-Term Outcomes of One-Step and Two-Step Sleeve Gastrectomy as Revision Procedures for Failed Adjustable Gastric Banding Compared With Those After Primary Sleeve Gastrectomy - Thaher, Omar; Driouch, Jamal; Hukauf, Martin; Köckerling, Ferdinand; Stroh, Christine (Frontiers in Surgery, 2021)
Background: The practice of bariatric surgery was studied using the German Bariatric Surgery Registry (GBSR). The focus of the study was to evaluate whether revision surgery One-Step (OS) or Two-Step (TS) sleeve gastrectomy (SG) has a large benefit in terms of perioperative risk in patients after failed Adjustable Gastric Banding (AGB). Methods: The data collection includes patients who underwent One-Step SG (OS-SG) or Two-Step SG (TS-SG) as revision surgery after AGB and primary SG (P-SG) between 2005 and 2019. Outcome criteria were perioperative complications, comorbidities, 30-day mortality, and operating time. Results: The study analyzed data from 27,346 patients after P-SG, 320 after OS-SG, and 168 after TS-SG. Regarding the intraoperative complication, there was a significant difference in favor of P-SG and TS-SG compared to OS-SG (p<0.001). The incidence of pulmonary complications was significantly higher in the OS-SG (p<0.001). There was also a significant difference in occurrence of staple line stenosis in favor of TS-SG (p=0.005) and the occurrence of sepsis (p=0.008). The mean operating time was statistically longer in the TS-SG group than in the OS-SG group (p<0.001). The 30-day mortality was not significantly different between the three groups (p=0.727). Conclusion: In general, our study shows that converting a gastric band to a SG is safe and feasible. However, lower complications were obtained with TS-SG compared to OS-SG. Despite acceptable complication and mortality rates of both procedures, we cannot recommend any surgical method as a standard procedure. Proper patient selection is crucial to avoid possible adverse effects.